Reconstruction of the Concept of Islamic Educational Public Relations in the Qur’an through Ibn ‘Araby’s Symbolic Metaphors - Bulqis Bulqis; Muhammad Fadhil Hadziq; Sri Jomila Oktari (Al-Munawwarah: Journal of Islamic Education, 2026)
This study aims to examine the concept of public relations in Islamic education from a Qur’anic perspective by employing Ibn ‘Araby’s symbolic–metaphorical approach. The research is motivated by the tendency to understand public relations in Islamic educational institutions primarily as a technical–managerial function, which often overlooks its normative, ethical, and spiritual dimensions. This study adopts a qualitative library research method, utilizing primary sources such as the Qur’an, classical and contemporary tafsir works, and Ibn ‘Araby’s major writings, including Fuṣūṣ al-Ḥikam and al-Futūḥāt al-Makkiyyah. Data analysis is conducted through thematic analysis and a hermeneutic–philosophical approach to reconstruct a Qur’an-based model of public relations in Islamic education. The findings indicate that public relations in Islamic education constitutes an integral part of the Islamic value system, functioning to build social, moral, and spiritual relationships between educational institutions and society. Qur’anic communication principles—such as qaulan sadīdan, qaulan balīghan, qaulan ma‘rūfa, qaulan karīma, qaulan layyina, and qaulan maysūra—serve as normative foundations for ethical and effective communication. The integration of Ibn ‘Araby’s symbolic metaphor approach enriches Islamic educational public relations with a transformative dimension, positioning communication as a meaningful, ethical, and spiritually grounded process that fosters public trust and social harmony.